Soil abiotic and microbial legacies jointly contribute to growth of invasive Solidago canadensis - Shu-Qi Zhou; Zuo-Fu Wei; Yu-Fei Zhao; Li-Jia Dong (Global Journal of Ecology - Peertechz Publications, 2019)
The invasion success of exotic plants strongly depends on soil properties of new ranges, however, little is known about the joint contribution of soil abiotic and biotic legacies to this success. To address the role of soil abiotic and microbial properties in plant invasions and associated mechanisms, we conducted two complementary experiments. In the fi rst experiment, we grew invasive Solidago canadensis in regular soils from its different invasion stages and measured plant growth to address the joint contribution of soil abiotic and microbial properties. In a second experiment, we set up four sterilization × three sites treatments and measured plant growth to address the infl uence of different soil microbes on S. canadensis. The growth of S. canadensis was constrained by soil N and bacteria, and was positively correlated to its leaf area and root area, but not its leaf chlorophyll contents and root hydraulic conductivity.